2009
DOI: 10.2119/molmed.2009.00100
|View full text |Cite
|
Sign up to set email alerts
|

Human Ghrelin Ameliorates Organ Injury and Improves Survival after Radiation Injury Combined with Severe Sepsis

Abstract: In the terrorist radiation exposure scenario, radiation victims are likely to suffer from additional injuries such as sepsis. Our previous studies have shown that ghrelin is protective in sepsis. However, it remains unknown whether ghrelin ameliorates sepsis-induced organ injury and mortality after radiation exposure. The purpose of this study is to determine whether human ghrelin attenuates organ injury and improves survival in a rat model of radiation combined injury (RCI) and, if so, the potential mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 53 publications
3
34
0
Order By: Relevance
“…On the other hand, the current findings demonstrate that ghrelin treatment depressed MPO activity and ROS generation, and helped to repair the BBB, suggesting that the protective effects of ghrelin in SAH-induced brain injury is mediated in part by blocking tissue neutrophil infiltration and the associated ROS-induced damage. In accordance with the present data, it was previously shown that ghrelin ameliorates organ injury in several inflammation models by inhibiting proinflammatory cytokine production and myeloperoxidase activity (Brzozowski et al, 2006;Iseri et al, 2008;Kasımay et al, 2006;Sehirli et al, 2008;Shah et al, 2009;Wu et al, 2008). Furthermore, ghrelin has been shown to exhibit anti-inflammatory functions against T cells and macrophages by inhibiting mononuclear cell binding and nuclear factor-kB activation (Chorny et al, 2008;Dixit et al, 2004;Li et al, 2004;Wassem et al, 2008).…”
supporting
confidence: 90%
“…On the other hand, the current findings demonstrate that ghrelin treatment depressed MPO activity and ROS generation, and helped to repair the BBB, suggesting that the protective effects of ghrelin in SAH-induced brain injury is mediated in part by blocking tissue neutrophil infiltration and the associated ROS-induced damage. In accordance with the present data, it was previously shown that ghrelin ameliorates organ injury in several inflammation models by inhibiting proinflammatory cytokine production and myeloperoxidase activity (Brzozowski et al, 2006;Iseri et al, 2008;Kasımay et al, 2006;Sehirli et al, 2008;Shah et al, 2009;Wu et al, 2008). Furthermore, ghrelin has been shown to exhibit anti-inflammatory functions against T cells and macrophages by inhibiting mononuclear cell binding and nuclear factor-kB activation (Chorny et al, 2008;Dixit et al, 2004;Li et al, 2004;Wassem et al, 2008).…”
supporting
confidence: 90%
“…Combined injuries promotes bacterial translocation and, therefore, ileus seen in our model, at least partially, supports the hypothesis that gut damage drives lung injury. Indeed, suppression of inflammation in the gut by administration of ghrelin in the model of combined radiation and sepsis injury suppressed neutrophil infiltration in lungs, also supporting our hypothesis (12). …”
Section: Discussionsupporting
confidence: 86%
“…In preclinical studies radiation has been combined with a number of different injuries (1, 4) including burns (911), sepsis (12), incisional wounds (13) and hemorrhage (14). These studies show the increased lethality in combined injuries, more severe tissue damage and the importance of timing of the wounding for survival.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of ghrelin’s protection towards inflammatory responses in various pathological conditions has been unraveling over the past few years. In this regard, we have previously shown that subdiaphragmatic vagotomy in rats prevents the anti-inflammatory effects of ghrelin in sepsis, radiation combined injury and gut I/R injury 28,29,57 . In the present study, we showed that ghrelin’s protective effect in renal I/R injury is indeed mediated by the vagus nerve.…”
Section: Discussionmentioning
confidence: 95%